Characterization of ion-exchanged zeolites with lithium for Pressure Swing Adsorption (PSA) applications - Nidya Jullanar Salman; Dhimas Satria; Damar Abi Ramadani; Teguh Kurniawan (Institut Teknologi Dirgantara Adisutjipto, 2022)
The method used for the Ion Exchange process to determine the characteristics of the zeolite is refluxing the zeolite using a 4 M LiCl solution for 36 hours at a temperature of 72℃ and calcined at a temperature of 400℃ for 10 hours. XRF characterization results showed natural zeolite Lampung had moderate Si/Al levels with 8.97 and 8.79 for those given lithium, while zeolite 13X had low Si/Al levels with 4.31 and 3.77 for those given lithium. The XRD results show that Lampung's natural zeolite is clinoptilolite and 13X zeolite is NaX. The results of the adsorption test using the PSA tool, namely for natural zeolite Lampung, the highest oxygen value was 21.3% and that was given lithium at 21.2% for the single bed and double bed types. For zeolite 13X, the highest oxygen value was 22% and that given lithium was 24% for the single bed type, and for the double bed type the highest oxygen value was 21.8% and those given lithium were 24.9%.